Environmental Exposure, Obesity, and Parkinson’s Disease: Lessons from Fat and Old Worms - Aitlhadj, Layla (National Institute of Environmental Health Sciences, 2011)
BACKGROUND: A common link has been exposed, namely, that metal exposure plays a role in obesity and in Parkinson’s disease (PD). This link may help to elucidate mechanisms of neurotoxicity. OBJECTIVE: We reviewed the utility of the nematode, Caenorhabditis elegans, as a model organism to study neurodegeneration in obesity and Parkinson’s disease (PD), with an emphasis on the neurotransmitter, dopamine (DA). DATA SOURCES: A PubMed literature search was performed using the terms “obesity” and any of the following: “C. elegans,” “central nervous system,” “neurodegeneration,” “heavy metals,” “dopamine” or “Parkinson’s disease.” We reviewed the identified studies, including others cited therein, to summarize the current evidence of neurodegeneration in obesity and PD, with an emphasis on studies carried out in C. elegans and environmental toxins in the etiology of both diseases. DATA EXTRACTION AND DATA SYNTHESIS: Heavy metals and DA have both been linked to diet-induced obesity, which has led to the notion that the mechanism of environmentally induced neurodegeneration in PD may also apply to obesity. C. elegans has been instrumental in expanding our mechanism-based knowledge of PD, and this species is emerging as a good model of obesity. With well-established toxicity and neurogenetic assays, it is now feasible to explore the putative link between metal-and chemical-induced neurodegeneration. CONCLUSIONS: One side effect of an aging population is an increase in the prevalence of obesity, metabolic disorders, and neurodegenerative orders, diseases that are likely to co-occur. Environmental toxins, especially heavy metals, may prove to be a previously neglected part of the puzzle.